2015
DOI: 10.5455/ijmsph.2015.0806201458
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity, nature of job, and exercise with the prevalence of essential hypertension in the Tharparkar desert

Abstract: Results: After getting approval from the ethics review committee, the mean age and prevalence of EHTN among the studied 563 participants from Tharparkar desert were assessed and found to be 37 (±16.4 years, range 10-82 years) and 81 (14.4%), respectively. Participants leading a sedentary lifestyle showed higher prevalence of EHTN (19.2%) than those leading an active lifestyle (1.9%). Participants having job with mild physical activity had higher prevalence of EHTN (19.4%) than those having jobs with active lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…This was caused by the habits of homemakers, who tended to be less active because they spent a lot of time at home, which in turn could increase the risk of hypertension. 13 Khakim et al (2022) suggested a correlation between work and physical activity in adults aged 20-39. Based on subjects who work in offices they had a lower level of activity compared to self-employed people who work outside.…”
Section: Discussionmentioning
confidence: 99%

The correlation between physical activity and hypertension in menopausal women

I Gusti Ayu Agung Anindya Maharani,
Putu Ayu Sita Saraswati,
I Gusti Ayu Artini
et al. 2024
ptji
“…This was caused by the habits of homemakers, who tended to be less active because they spent a lot of time at home, which in turn could increase the risk of hypertension. 13 Khakim et al (2022) suggested a correlation between work and physical activity in adults aged 20-39. Based on subjects who work in offices they had a lower level of activity compared to self-employed people who work outside.…”
Section: Discussionmentioning
confidence: 99%

The correlation between physical activity and hypertension in menopausal women

I Gusti Ayu Agung Anindya Maharani,
Putu Ayu Sita Saraswati,
I Gusti Ayu Artini
et al. 2024
ptji
“…Patients with a volvulus typically present to the emergency room with various non-specific gastrointestinal symptoms, including abdominal pain, abdominal distension, vomiting, or constipation, all of which indicate LBO, but with no exact cause. Physical examination findings also vary considerably with abdominal tenderness and distension being the most common to the presentation of a mass in the abdomen in some cases [4][5]. Laboratory investigations are not sufficiently helpful in cases of cecal volvulus [6].…”
Section: Discussionmentioning
confidence: 99%